Methodologies for using performance measurement - Cinquini, Lino; Mitchell, Falconer; Nørreklit, Hanne; Tenucci, Andrea (Proceedings of Pragmatic Constructivism, 2011)
The speech explores the operational dynamics of a PMS at the interface between a parent company and its subsidiary. The research is based on two case studies. The companies are both subsidiaries of US multinational companies located in Italy. Both are market leaders of different sectors and governed by different strategic mentalities and managerial methodologies that reflect the specific business strategy adopted by the parent company. The methodologies of performance management in use by the two companies are addressed respectively as pragmatic constructivism and pre- categorized analytical data paradigm. Drawing on the narrative of the two cases we conclude that these two methodologies of performance management use support two alternative views of strategy: competitive advantage and resource-based view. The findings show that it is not simply the structure or technical design of a PMS that will determine its impact on an organization and ultimately its practical success but also the strategic mentality that underpins its functional rationale.